The Cause of Kidney Stone Formation and Treatment from the Perspective of Conventional and Traditional Persian Medicine - Maryam Rameshk (Traditional and Integrative Medicine, 2024)
Urinary stone disease is the most common urinary tract disease that has caused human suffering since ancient times. The observation of a 7000-year-old bladder stone in an Egyptian skeleton proves this claim. This disease causes many complications for patients, but its pathogenesis is unclear. The knowledge about the cause of urinary stones formation and treatment recommendations from ancient physicians' perspectives is probably helpful in preventing and treating kidney stones. Data for this review were provided by search in five Traditional Persian sources available, including Canon of Medicine (Avicenna, 980-1037 AD), Kamil al–Sana al-Tibbiya (Majusi Ahwazi (Haly Abbas), died 982-994), Zakhire Kharazmshahi (Jorjani, 1042-1137 AD), Makhzan al Adviyeh (Mohammad Hossein Aghili Khorasani Shirazi in 18th AD), and Tib-e-Akbari (Mohammad Akbar Arzani-11th and 12th centuries AD) and Until January of 2023, all English publications in Science Direct, PubMed, Google Scholar and Scopus, using various search terms such as urolithiasis, lithiasis, and kidney stone. Some dietary recommendations in Traditional Persian Medicine (TPM) for treatment of urinary tract stones and 134 recommended plant species, in addition to studies of in vivo effects of some of them in conventional medicine have been described in this article. The TPM with long experience and special principles has good potential in the field of diagnosis and treatment in its own way and can act as a strong complementary treatment system for diseases that have challenging treatment. It seems using the experiences in the TPM sources and relying on today's knowledge can create a way to prevent the formation and recurrence of urinary tract stones